EFFECT OF PLASMA ANGIOTENSIN CONVERTING ENZYM IN ERECTILE DYSFUNCTION - Sinrang, Andi Wardihan (Indonesian Urological Association, 2014)
Objective:The aim of this study was to know the effect of aging and I/D angiotensin converting enzymes (ACE) gene polymorphisms in modulating plasma ACE level in erectile dysfunction(ED) subjects.Material & method:This case control study carried out in Makassar with 83 male subjects (49 ED subjects and 34 normal subjects). International Index of Erectile Function-5 was used for ED diagnosis while plasma ACE level and genotyping ACE gene examined with ELISA test and Rigat PCR method respectively.Results:The data showed that plasma ACE level siginificantly higher in ED group compared to normal group, while the plasma ACE level consistently raised following the increased of age in ED group but did not statistically significant (p>0.05) compare to normal group. DD genotype in ED group had mean plasma ACE higher compared to ID and II subjects eventhough did not statistically significant.Conclusion: The high level of ACE plasma appeared to have a pivotal rule in ED mechanisms as well as in older ED subjects. DD genotype partly modulated the raising of plasma ACE in ED subject comprared to ID and II genotype. Keywords: Plasma ACE level, erectile dysfunction.